Improving knowledge, technical skills, and confidence among pediatric health care providers in the management of chronic tracheostomy using a simulation model. Issue 7 (17th December 2015) - Agarwal, Amit; Marks, Nancy; Wessel, Valerie; Willis, Denise; Bai, Shasha; Tang, Xinyu; Ward, Wendy L.; Schellhase, Dennis E.; Carroll, John L.
Summary: Objective: The results from a recent national survey about catastrophic complications following tracheostomy revealed that the majority of events involved a loss of airway. Most of the events due to airway loss involved potentially correctable deficits in caregiver education. Training in a simulated environment allows skill acquisition without compromising patient safety. We assessed the knowledge and confidence level of pediatric health care providers at a large tertiary care children's hospital in routine and emergency tracheostomy care and evaluated the efficacy of a comprehensive simulation‐based tracheostomy educational program. Methods: The prospective observational study was comprised of 33 subjects including pediatric residents, internal medicine–pediatric residents, pediatric hospitalist faculty physicians, and advanced practice registered nurses who are involved in the care of patients with tracheostomies within a tertiary‐care children's hospital. The subjects completed self‐assessment questionnaires and objective multiple‐choice tests before and after attending a comprehensive educational course that employed patient simulation. The outcome measurements included pre‐ and post‐course questionnaires, pre‐ and post‐course test scores, and observational data from the simulation sessions. Results: Before the education and simulation, the subjects' comfort and confidence levels on a five‐point Likert scale in performing routine tracheostomy tube care, routine tracheostomy tube change, and an emergency tracheostomy tube change were as follows (median (Q1, Q3)): 1 (1, 2), 1 (1, 2), and 1 (1, 2), respectively (n = 28). The levels of comfort and confidence after completing the course improved significantly to 4 (4, 5), 4 (4, 5), 4 (4, 5), respectively ( P  < 0.001) (n = 20). For the knowledge assessment, the pre‐course test mean score was 0.53 ± 0.50, and the scores on the post‐course test improved significantly with a mean score of 0.82 ± 0.39 ( P  < 0.001). During the educational intervention, specific deficiencies observed included a lack of understanding or familiarity with different types of tracheostomy tubes (e.g., cuffed versus uncuffed), physiological significance of the cuff, mechanism of action and physiological significance of the speaking valve, and the importance of the obturator in changing the tracheostomy tube. Conclusion: There is a need for improved tracheostomy education among pediatric health care providers. Incorporation of patient‐simulation into a tracheostomy educational program was effective in improving knowledge, confidence, and skills.Pediatr Pulmonol. 2016;51:696–704 . © 2015 Wiley Periodicals, Inc.